Benthic Community and Assessment of Water Quality Using Biological Index in RAMSAR, Ninh Binh - Nhuong, Do Van; Hai, Tran Nam; Nga, Nguyen Thi; Hau, Tran Duc (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 4, 2021)
Van Long, the largest wetland RAMSAR in delta areas of northern Vietnam, is a famous destination for tourists, which might influence on water quality and biodiversity. Two surveys in September 2019 and May 2020 aimed to determine species composition of macrozoobenthos and build biological indicators to assess the water quality for biodiversity conservation. Present findings report a list of 41 species in 27 genera, 14 families of macrozoobenthos (Gastropoda, Bivalvia, Crustacea - Decapoda) in Van Long. Of which, Gastropoda is the most abundant, accounting for 58.5% of the total number of species, followed by Crustacean (26.8%) and Bivalvia (14.6%). Both Shannon-Weiner biodiversity (H') and Margalef indices “d” in rainy season are higher than those in dry season (H '= 2.565 vs. 2.466 and d = 4.987 vs. 3.286, respectively). For water quality assessment, based on TCVN 7220-2: 2002, the water in Van Long RAMSAR is in low level of pollution. According to ASPT index on average (3.42), this parameter was under medium to heavily polluted. The results recommend utilizing family taxon of macrozoobenthos with the recorded scales to assess quality of aquatic environments of freshwater bodies in northern Vietnam.